A new species of Denisiella (Collembola: Sminthurididae) from Panama and new records for D. sexpinnata (Denis, 1938) - Palacios-Vargas, José G. (Zootaxa, 2007)
Denisiella diomedesi sp. nov. from Panama is described and illustrated based on male specimens. It is close to D. maesorum from Nicaragua, but possesses a nasal organ. New localities for D. sexpinnata (Denis, 1931) from Mexico and Nicaragua are provided.